2020
DOI: 10.3390/biomedicines8120606
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Biomarker Panel to Distinguish Risk of Progressive Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) patients typically progress to kidney failure, but the rate of progression differs per patient or may not occur at all. Current CKD screening methods are sub-optimal at predicting progressive kidney function decline. This investigation develops a model for predicting progressive CKD based on a panel of biomarkers representing the pathophysiological processes of CKD, kidney function, and common CKD comorbidities. Two patient cohorts are utilised: The CKD Queensland Registry (n = 418… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Urinary or serum proteomics for the study of DKD produced compelling results, [108][109][110] which could be conjugated with metabolomics for integrative analysis. For instance, Liu et al 104 concluded that the accuracy of DKD prediction could be improved by performing integrative serum proteomics and metabolomics data analysis Owens et al 111 aimed to develop a model for predicting progressive kidney damage based on a biomarker panel of serum creatinine, osteopontin, tryptase, urea and eGFR. Owens and collaborators obtained an accuracy of 84.3% in predicting future progressive chronic kidney disease at baseline, greater than eGFR (66.1%), sCr (67.7%), albuminuria (53.2%), or albumin-creatinine ratio (53.2%).…”
Section: Towards the Future: Multi-omics Analysis And Panels Of Bioma...mentioning
confidence: 99%
“…Urinary or serum proteomics for the study of DKD produced compelling results, [108][109][110] which could be conjugated with metabolomics for integrative analysis. For instance, Liu et al 104 concluded that the accuracy of DKD prediction could be improved by performing integrative serum proteomics and metabolomics data analysis Owens et al 111 aimed to develop a model for predicting progressive kidney damage based on a biomarker panel of serum creatinine, osteopontin, tryptase, urea and eGFR. Owens and collaborators obtained an accuracy of 84.3% in predicting future progressive chronic kidney disease at baseline, greater than eGFR (66.1%), sCr (67.7%), albuminuria (53.2%), or albumin-creatinine ratio (53.2%).…”
Section: Towards the Future: Multi-omics Analysis And Panels Of Bioma...mentioning
confidence: 99%
“…This finding has implications beyond AKI, as tissue injury due to various causes can raise OPN serum levels in humans, including but not limited to direct lung injury by COVID-19, bacterial pneumonia ( 46 ), sepsis from various causes ( 32 , 47 , 48 ), or cardiac injury ( 44 , 47 ). OPN has also been described as a marker of kidney injury and declining kidney function, as example ( 49 , 50 ), but not much is known about the mechanisms involved. All these conditions are highly associated with multiorgan failure, particularly AKI and ALI or its most severe form, ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…OPN has also been described as a marker of kidney injury and declining kidney function e.g. 53,54 , but not much is known about the mechanisms involved. All these conditions are highly associated with multiorgan failure, in particular AKI and ALI or its most severe form acute respiratory distress syndrome (ARDS).…”
Section: Discussionmentioning
confidence: 99%